2020
DOI: 10.3389/fonc.2020.00284
|View full text |Cite
|
Sign up to set email alerts
|

LOXL2 Expression Status Is Correlated With Molecular Characterizations of Cervical Carcinoma and Associated With Poor Cancer Survival via Epithelial-Mesenchymal Transition (EMT) Phenotype

Abstract: As molecular analyses based on high-throughput sequencing have developed, the molecular classification of cancer has facilitated clinical work. The aim of the present study was to identify a new potential therapeutic target for cervical carcinoma by molecular analyses. We firstly tested the LOXL2 expression pattern in 50 paired normal cervix and cervical carcinoma via qPCR and immunohistochemistry, and the LOXL2 expression pattern was found to be in accordance with public datasets from Gene Expression Omnibus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…However, resistance of cancer cells has limited its efficacy. EMT is a potential factor in stimulation of chemoresistance via elevating proliferation and invasion of cancer cells ( Cao et al, 2020 ). The TGF-β can induce EMT and its inhibition by miR-145 suppresses malignant behavior of cancer cells ( Chen et al, 2020a ).…”
Section: Curcumin and Transforming Growth Factor-beta In Different DImentioning
confidence: 99%
“…However, resistance of cancer cells has limited its efficacy. EMT is a potential factor in stimulation of chemoresistance via elevating proliferation and invasion of cancer cells ( Cao et al, 2020 ). The TGF-β can induce EMT and its inhibition by miR-145 suppresses malignant behavior of cancer cells ( Chen et al, 2020a ).…”
Section: Curcumin and Transforming Growth Factor-beta In Different DImentioning
confidence: 99%
“…So far, the identi ed tumor-derived soluble factors are still very limited for triggering pre-metastatic niche formation in HCC. LOXL2 upregulation has been identi ed to promote metastasis of gastric, breast and colorectal cancer [34][35][36], and implicates in less differentiation [37] and poor prognosis [35,38], implying a positive correlation between LOXL2 level and tumor metastasis. Except that, hypoxia-associated LOXL2 and LOX also exhibit a potential induction role in the formation of pre-metastatic niche in HCC and breast cancer [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…15 Cao Canhui et al found that over-expression of LOXL2 significantly predicts poor survival in cervical cancer via remolding epithelial-mesenchymal transition (EMT). 16 Before carrying out the research, we have found that some LOX family genes, such as LOX and LOXL2, were significantly correlated with poor prognosis in many types of solid tumors (eg, bladder urothelial carcinoma, lung squamous cell carcinoma, and skin cutaneous carcinoma) using the online web tool ESurv, which was a user-friendly web tool for survival analysis. 17 Here, we aimed to comprehensively explore the expression level, prognostic values, and mutation characteristics of LOX family genes in KIRC, and identify promising biomarkers that may play key roles in the occurrence and development of KIRC.…”
Section: Introductionmentioning
confidence: 99%
“…Hiroaki Kasashima et al found LOXL1, LOXL3, and LOXL4 are significantly correlated with distant metastasis in gastric cancer 15 . Cao Canhui et al found that over‐expression of LOXL2 significantly predicts poor survival in cervical cancer via remolding epithelial‐mesenchymal transition (EMT) 16 …”
Section: Introductionmentioning
confidence: 99%